Expression of the full length NS2B integral membrane protein, a cofactor for dengue protease. - Kwek, Stanley Ming Kun. (2009)
Polyprotein processing of dengue virus is performed by the host signal peptidase and virus encoded two-component protease consisting of NS3 and its cofactor NS2B. The exact mechanism by which NS2B cofactor stimulates the NS3 protease is not known and structure of complete NS2B is still lacking. To study the role of NS2B cofactor in the protease activity, we expressed in Escherichia coil the full length NS2B integral membrane protein together with dengue serotype 2 NS3 of various truncations, namely, NS2B-NS371aa, NS2B-NS3Pro and NS2B-NS3FL. The expression of functional and soluble NS2B-NS3Pro and NS2B-NS3FL proteins, showed high level of protease activity as auto-proteolysis at several sites of the protein were observed. NS2B-NS371aa which yielded an intact protein band was chosen for protein purification for the purpose of obtaining intact and pure NS2B with truncated NS3. The highest expression level of NS2B-NS371aa was by the auto-induction expression. Detergent solubilization with n-dodecyl-β-d-maltoside was effective that extracted the largest quantity of soluble NS2B-NS371aa. Ni-NTA affinity chromatography together with cation exchange chromatography proved useful in removing most Escherichia coil proteins during purification but the low expression level associated with NS2B-NS371aa remains a major hurdle. This study serves as a foundation and forms the preliminary work towards hydrophobic studies on full length NS2B integral membrane protein.